2017
DOI: 10.1002/prot.25222
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic α helix propensities compact hydrodynamic radii in intrinsically disordered proteins

Abstract: Proteins that lack tertiary stability under normal conditions, known as intrinsically disordered, exhibit a wide range of biological activities. Molecular descriptions for the biology of intrinsically disordered proteins (IDPs) consequently rely on disordered structural models, which in turn require experiments that assess the origins to structural features observed. For example, while hydrodynamic size is mostly insensitive to sequence composition in chemically denatured proteins, IDPs show strong sequence-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(87 citation statements)
references
References 121 publications
(279 reference statements)
2
85
0
Order By: Relevance
“…ID regions were predicted from the primary sequences using the GeneSilico MetaDisorder service (Kozlowski and Bujnicki, 2012). For the identified ID regions, R h was then predicted using the net charge and intrinsic chain propensity for the polyproline II backbone conformation, both known to promote elongated hydrodynamic dimensions in disordered ensembles (Tomasso et al, 2016; English et al, 2017, 2019). Comparing the IDP set of experimental R h to the set of predicted R h from PS IDPs, two observations are immediately apparent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ID regions were predicted from the primary sequences using the GeneSilico MetaDisorder service (Kozlowski and Bujnicki, 2012). For the identified ID regions, R h was then predicted using the net charge and intrinsic chain propensity for the polyproline II backbone conformation, both known to promote elongated hydrodynamic dimensions in disordered ensembles (Tomasso et al, 2016; English et al, 2017, 2019). Comparing the IDP set of experimental R h to the set of predicted R h from PS IDPs, two observations are immediately apparent.…”
Section: Resultsmentioning
confidence: 99%
“…A key difference between the two IDP sets is that the non-phase separating protein data uses experimental R h , while the PS IDP set uses sequence predicted values. The methods developed to predict R h from sequence for IDPs (Marsh and Forman-Kay, 2010; Tomasso et al, 2016; English et al, 2017) were found to be accurate when tested (Perez et al, 2014; English et al, 2019), and the IDPs used here consist primarily of the same IDPs that were used to train the predictions. R h for these IDPs are thus accurately predicted from sequence ( Supplementary Information, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While chemically denatured proteins are known to adopt macromolecular sizes that depend weakly on sequence details other than chain length [ 36 ], IDPs in water exhibit strong sequence-dependent influences on structural size [ 37 ]. Computer simulations show that steric effects on disordered structure cannot account for the hydrodynamic size dependence on sequence observed in IDPs [ 38 ]. Additionally, temperature changes are found to induce large shifts in the hydrodynamic size for disordered proteins in water [ 39 , 40 , 41 ] that can exceed the change in size associated with the heat denaturation of folded proteins of the same chain length [ 42 ].…”
Section: Introductionmentioning
confidence: 99%